DEVELOPMENT OF INTEGRATED SCIENCE DIGITAL MODULE BASED ON SCIENTIFIC LITERACY - Retna Kusuma Astuti; Muriani Nur Hayati (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2019)
Student quality of Science education program in the University of Pancasakti Tegal which is prepared to be science teacher candidates in junior high school in the future needs to be enhanced, because they must improve student scientific literacy ability. Students were expected to have scientific literacy competence and advanced in internet technology. Thus, research objectives were determining validity, reading level, and module effectiveness. It was development research. Subject of this reasearch is Students of Science Education study program in University of Pancasakti Tegal, semester IV, 2017/2018 academic year. The first step was fulfilling validity criteria, reading level and then trying out to determine learning effectiveness. Data analyze used judgment expert method, t-test and gain test. It concluded that the Integrated Science digital module based on scientific literacy was valid for learning with a score of 26 (high), easy understanding in reading level , it was useful to enhance cognitive learning outcome students that could be seen from classical learning outcome total of experiment class of 82.35% and control class of 52.94%. Gain result and t-test showed that there was a significant difference between experiment class and control class, it was 4.057, gain test for experiment class was g = 0.31and control class of g = 0.24.